ChemInform Abstract: Catalytic Reversible Alkene‐Nitrile Interconversion Through Controllable Transfer Hydrocyanation. Issue 19 (April 2016) - Fang, Xianjie; Yu, Peng; Morandi, Bill
Abstract: Review: 40 refs.